2022
DOI: 10.1007/s00417-022-05803-6
|View full text |Cite
|
Sign up to set email alerts
|

The intraocular implant and visual rehabilitation improve the quality of life of elderly patients with geographic atrophy secondary to age-related macular degeneration

Abstract: Introduction The objective of this prospective study was to evaluate the effects of intraocular macular lens implantation and visual rehabilitation on the quality of life of patients with geographic atrophy (GA) secondary to age-related macular degeneration (AMD). Methods Patients with bilaterally decreased near vision (not better than 0.3 logMAR with the best correction), pseudophakia, were included in the project. The Scharioth macula lens (SML) was imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It encompasses numerous services that help to enhance low vision including prescription eyewear, visual aids like magnifying glasses, and learning skills to better manage everyday activities 22 . A recent study concluded that the implantation of the Scharioth macula lens in the better-seeing eye of GA patients followed by visual rehabilitation enhanced near vision and alleviated mental health signs related to vision 32 . According to another study, visual training in patients with AMD leads to improvements in fixation stability, reading speed, and visual acuity 24 .…”
Section: Resultsmentioning
confidence: 99%
“…It encompasses numerous services that help to enhance low vision including prescription eyewear, visual aids like magnifying glasses, and learning skills to better manage everyday activities 22 . A recent study concluded that the implantation of the Scharioth macula lens in the better-seeing eye of GA patients followed by visual rehabilitation enhanced near vision and alleviated mental health signs related to vision 32 . According to another study, visual training in patients with AMD leads to improvements in fixation stability, reading speed, and visual acuity 24 .…”
Section: Resultsmentioning
confidence: 99%
“…A few studies investigated the effect of visual rehabilitation, Nekolova et al. (2023) showed that implantation of a magnifying add‐on lens implant followed by intensive visual rehabilitation for 20 days had a significant positive effect on performing near activities and upturns in mental health symptoms related to vision. It is unclear if the effect was caused by rehabilitation or implantation of the magnifying lens.…”
Section: Visual Rehabilitationmentioning
confidence: 99%
“…Training to improve eye movement control has also been shown to increase reading speed in patients with AMD 30 . Rehabilitation techniques utilizing microperimetry and intraocular implants have also shown varying degrees of effectiveness in improving visual outcomes 31,32 . While maximizing patients’ remaining vision is essential for preserving the quality of life, a more robust solution to slow or even halt the inevitable decline of vision from worsening GA is desperately needed.…”
Section: Current Treatmentmentioning
confidence: 99%